Porous carbon, silicon carbon negative electrode material, electrode plate, lithium ion battery and electric appliance

A porous carbon matrix with a Luan-shaped pore distribution in the 1-3 nm range addresses silicon loading inefficiencies, resulting in a silicon-carbon negative electrode material with high capacity and low expansion, improving electrochemical performance.

CN119252896AActive Publication Date: 2025-01-03JIANGXI ZICHEN TECH CO LTD

Patent Information

Application Number
CN202411381145.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing porous carbon matrices for silicon-carbon anode materials have poor silicon loading efficiency, leading to inadequate electrochemical performance due to mismatched pore structures, high pore resistance, and difficulty in achieving simultaneous high adsorption capacity and rate, as well as lithium ion deintercalation.

Method used

A porous carbon material with a specific pore distribution, comprising micropores and mesopores, featuring a Luan-shaped distribution in the 1-3 nm range, ensuring low pore resistance and high silicon loading efficiency, along with a silicon-carbon negative electrode material containing nano-silicon in these pores, and a coating layer for improved electrical properties.

Benefits of technology

The solution results in a silicon-carbon negative electrode material with high capacity, high initial efficiency, and low expansion rate, enhancing the electrochemical performance by optimizing pore structure and silicon distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252896A_ABST
    Figure CN119252896A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrode materials, in particular to porous carbon, a silicon-carbon negative electrode material, an electrode plate, a lithium ion battery and an electric appliance. The porous carbon has micropores and mesopores, and the percentage of the pore volume of pores with the pore diameter smaller than 3 nm in the total pore volume is higher than 85%; the percentage of the pore volume of pores with the pore diameter less than 0.7 nm in the total pore volume is less than 15%; the pore size distribution of the porous carbon is in a Koelreuteria-type distribution, and the Koelreuteria-type distribution is that Dv / Dw of a pore size distribution curve is greater than 0.05 cm < 3 >. G <-1 >. Nm <-1 > in a pore size interval of 1-3nm. The porous carbon provided by the invention is micro-mesoporous porous carbon, is distributed in a koelreuteria shape, is low in pore resistance, can improve the silicon loading efficiency, ensures the adsorption capacity and also ensures the de-intercalation of lithium ions, and the silicon-carbon negative electrode material prepared from the porous carbon is high in capacity and efficiency and lower in expansion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a porous carbon, silicon-carbon negative electrode material, an electrode sheet, a lithium-ion battery and an electrical appliance. Background Art

[0002] Porous carbon materials are widely used in gas separation, water purification, heterogeneous catalytic carrier materials, high-performance thermal field materials, etc. due to their unique surface properties and structures. They also have broad application prospects in new energy materials such as high-performance materials for lithium-ion batteries and high-performance materials for sodium-ion batteries. The rich pore structure, huge specific surface area and low cost are the main reasons why they have advantages in various fields.

[0003] As a new type of silicon-containing anode material, the silicon-carbon anode material prepared by depositing nanosilicon in a porous carbon matrix has a smaller volume effect and better cycle performance than pure silicon. However, the existing porous carbon matrix has poor silicon loading efficiency, which in turn affects the electrochemical performance of the silicon-carbon anode material. Summary of the invention

[0004] After in-depth research, the inventors of the present invention found that:

[0005] As the matrix of new silicon-carbon materials, the material structure of porous carbon is the core factor affecting the performance of silicon-carbon. The specific surface area and pore size distribution are the two most important factors affecting the electrochemical performance of porous carbon. At present, the porous carbon matrix used does not have transport pores that match the adsorption pore volume, the pore resistance is large, the silicon loading efficiency is low, and it is impossible to have a large adsorption capacity and a high adsorption rate at the same time, and it is impossible to take into account both the adsorption force and the lithium ion deintercalation.

[0006] In view of this, the present invention is proposed.

[0007] The first purpose of the present invention is to provide a porous carbon, which includes micropores and mesopores, and in the range of pore diameter of 1-3nm, the pore size distribution presents a Luan-shaped distribution, the pore resistance is small, the silicon loading efficiency is high, and the adsorption force can be guaranteed while also ensuring the deintercalation of lithium ions.

[0008] The second object of the present invention is to provide a silicon-carbon negative electrode material, which includes the porous carbon as described above and nano-silicon located in the pores of the porous carbon, and the silicon-carbon negative electrode material has high capacity, high first efficiency and small expansion.

[0009] A third object of the present invention is to provide an electrode sheet, which comprises the silicon-carbon negative electrode material as described above.

[0010] A fourth object of the present invention is to provide a lithium ion battery, comprising the electrode sheet as described above.

[0011] A fifth object of the present invention is to provide an electrical appliance comprising the lithium-ion battery as described above.

[0012] In the present invention, the electrical appliances may be, but are not limited to, mobile phones, tablet computers, laptop computers, electric toys, electric tools, battery vehicles, electric vehicles, ships, spacecraft, and the like.

[0013] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0014] A porous carbon, the porous carbon comprising micropores and mesopores, wherein the percentage of pore volume of pores with pore diameter less than 3 nm in the total pore volume is higher than 85%, and the percentage of pore volume of pores with pore diameter less than 0.7 nm in the total pore volume is lower than 15%; in a pore distribution curve obtained by nitrogen adsorption test, in which the abscissa is the pore diameter and the ordinate is the differential pore volume dV / dW, the porous carbon has a differential pore volume dV / dW greater than 0.05 cm in the pore diameter interval of 1-3 nm. 3 ·g -1 ·nm -1 .

[0015] Preferably, the porous carbon has at least one peak in the pore size range of 1-3 nm;

[0016] And / or, the porous carbon has at least one peak-valley in the pore size range of 1-3 nm, and the dV / dW of the lowest point of the peak-valley is greater than 0.1 cm 3 ·g -1 ·nm -1 .

[0017] Preferably, the microporosity of the porous carbon is 50%-90%.

[0018] Preferably, the pore volume of the porous carbon is 0.6-1.2 cc / g.

[0019] Preferably, the BET specific surface area of ​​the porous carbon is 1500-2500m 2 / g.

[0020] Preferably, the particle size Dv50 of the porous carbon is 3-10 μm, the particle size Dv99 of the porous carbon is 10-25 μm, and the particle size Dn10 of the porous carbon is 0.5-5 μm.

[0021] A silicon-carbon negative electrode material comprises the porous carbon described in any one of the aforementioned embodiments, and nano-silicon located in the pores of the porous carbon.

[0022] Preferably, the particle size Dv50 of the silicon-carbon negative electrode material is 3 to 10 μm, the particle size Dv99 of the silicon-carbon negative electrode material is 10 to 25 μm, and the particle size Dn10 of the silicon-carbon negative electrode material is 0.5 to 5 μm.

[0023] Preferably, the BET specific surface area of ​​the silicon-carbon negative electrode material is 0.5-30 m 2 / g.

[0024] Preferably, the tap density of the silicon-carbon negative electrode material is 0.5-2 g / cm 3 .

[0025] Preferably, the surface of the silicon-carbon negative electrode material further includes a coating layer; the coating layer contains at least one of amorphous carbon, a fast ion conductor and a high molecular polymer.

[0026] Preferably, the silicon content of the silicon-carbon negative electrode material is 5wt%-85wt%.

[0027] The method for preparing the silicon-carbon negative electrode material comprises the following steps:

[0028] The porous carbon is vapor-deposited in an atmosphere containing a silicon source to obtain the silicon-carbon negative electrode material.

[0029] Preferably, the method further comprises: coating the silicon-carbon negative electrode material to obtain a coating layer on the surface of the silicon-carbon negative electrode material, wherein the coating layer comprises at least one of amorphous carbon, a fast ion conductor and a high molecular polymer.

[0030] An electrode sheet, comprising the silicon-carbon negative electrode material according to any one of the aforementioned embodiments.

[0031] A lithium ion battery comprises the electrode sheet described in the above embodiment.

[0032] An electrical appliance comprises the lithium-ion battery described in the above embodiment.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The porous carbon provided by the present invention includes micropores and mesopores (which can be recorded as micro-mesoporous porous carbon), and in the range of pore diameter of 1-3nm, the pore size distribution is a Luan-shaped distribution. During the adsorption process, the adsorption pores (micropores) and the transport pores (small mesopores matching the micropores) cooperate with each other, and the pore resistance is low, which ensures the adsorption force of silicon sources (such as silane gases, etc.), and can improve the silicon loading efficiency. The uniformly variable pores (Luan-shaped distribution) also ensure the deintercalation of lithium ions. The silicon-carbon negative electrode material prepared by the porous carbon has high capacity and efficiency, and lower expansion rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 : is the pore distribution diagram of the porous carbon in Example 1 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume);

[0037] Figure 2 : is a pore distribution diagram of the porous carbon in Example 2 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume);

[0038] Figure 3 : is a pore distribution diagram of the porous carbon in Example 3 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume);

[0039] Figure 4 It is a pore distribution diagram of the porous carbon in Comparative Example 1 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume);

[0040] Figure 5 It is a pore distribution diagram of the porous carbon in Comparative Example 2 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume);

[0041] Figure 6 It is a pore distribution diagram of the porous carbon in Comparative Example 3 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume);

[0042] Figure 7 Schematic diagram of the aperture change of Luan-shaped holes;

[0043] Figure 8 Schematic diagram of the pore size change of the peak-shaped pore. DETAILED DESCRIPTION

[0044] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If the specific conditions are not indicated in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0045] The first aspect of the present invention provides a porous carbon, wherein the porous carbon includes micropores and mesopores, and the pore volume of pores with a pore size of less than 3 nm accounts for more than 85% of the total pore volume, for example, it can be 88%, 90%, 92%, 95%, 97%, 99%, 100%, etc., or other values ​​within the range; the pore volume of pores with a pore size of less than 0.7 nm accounts for less than 15% of the total pore volume, for example, it can be 14%, 13%, 12%, 11%, 10%, 8%, 5%, 1%, 0, etc., or other values ​​within the range; in a pore distribution curve obtained by a nitrogen adsorption method with the abscissa being the pore size and the ordinate being the differential pore volume dV / dW, the porous carbon has a differential pore volume dV / dW>0.05cm in the pore size range of 1-3nm. 3 ·g -1 ·nm -1 That is to say, the pore distribution curve has no intersection with the horizontal axis in the pore diameter range of 1-3nm (excluding the endpoint value) (the pore distribution curve has no intersection with the horizontal axis, which means that the differential pore volume dV / dW≠0), and the pore distribution curve will not be close to the horizontal axis in the pore diameter range of 1-3nm (the pore distribution curve is close to the horizontal axis, which means that the differential pore volume dV / dW≤0.05cm 3 ·g -1 ·nm -1 ).

[0046] In the present invention, according to the definition of the International Association of Pure and Applied Chemistry (IUPAC), micropores refer to pores with a pore size of less than 2nm, and mesopores refer to pores with a pore size of 2-50nm. Not subject to theoretical constraints, the relationship between the various pore volumes of porous carbon has an important influence on the dynamic adsorption performance and performance of porous carbon. If the porous carbon only has a developed adsorption pore volume but no transport pores to match it, the adsorption rate cannot be improved, and the role of the adsorption pores cannot be well played. On the contrary, although there are enough transport pores, there are not enough adsorption pores, and the adsorption performance is poor. As a porous carbon substrate for silicon deposition, it is not only necessary to have a large adsorption capacity, but also a higher adsorption rate.

[0047] The porous carbon provided by the present invention includes micropores and mesopores (which can be recorded as micro-mesoporous porous carbon). The porous carbon is used as a carrier and needs to adsorb cracked nano-silicon into the pores. Therefore, a certain amount of micropores is required as adsorption pores to ensure the adsorption force field; however, not all of them can be micropores. Lithium ions are easy to enter but difficult to exit when they are deintercalated in porous carbon materials with high microporosity (for example, microporosity>90%). Therefore, a certain amount of small mesopores are required to provide a transport channel to increase the adsorption rate while ensuring the deintercalation of lithium ions; and, without being bound by theory, the micro-mesopores can also effectively inhibit the expansion of silicon.

[0048] Not bound by theory, for pores with a pore size of less than 0.7 nm, it is difficult for vapor-phase silicon precursor molecules (such as silane molecules) to enter due to the small pore size, resulting in pores with a pore size of less than 0.7 nm being difficult to utilize. Therefore, too many pores with a pore size of less than 0.7 nm will lead to low micropore utilization, which needs to be controlled within 15%.

[0049] Without being bound by theory, pores smaller than 3 nm have two types of pore distribution, one is a peak distribution and the other is a Luan-shaped distribution.

[0050] Among them, the peak-type pore structure is mainly manifested in the interval of pore diameter of 1-3nm (excluding the endpoint value), the pore distribution curve has more than one intersection with the horizontal axis or is close to the horizontal axis, and further, in most cases, the peak-type pore structure has at least one peak in the interval of pore diameter of 1-3nm, and / or the porous carbon has at least one peak valley in the interval of pore diameter of 1-3nm, and the lowest point of the peak valley dV / dW is less than 0.05cm 3 ·g -1 ·nm -1 The characteristics of peak pore distribution are mainly manifested in that as the pore size increases, the pore distribution changes in a peak-to-valley manner, and the pore size transition is relatively steep. In the peak pore structure, the pore size distribution is discontinuous and the total number of pores is insufficient, such as Figure 8 As shown, the peak-shaped pores will suddenly change in diameter. When the pores are deeper and smaller in diameter, the resistance that nano-silicon has to overcome to enter is greater, and the relative distance that can diffuse (compared to the pore depth) is shorter. Therefore, the utilization rate of the pores is also lower.

[0051] The characteristics of Luan-shaped pore distribution are mainly manifested in that as the pore diameter increases, the pore distribution changes in a mountainous manner, and the pore diameter transition is relatively smooth and gentle. In the pore diameter range of 1-3nm, the pore distribution curve has no intersection with the horizontal axis, nor is it close to the horizontal axis, and the pore distribution is relatively uniform. The pores of the Luan-shaped structure have continuous and uninterrupted pore diameter distribution, a large number of total pores, and basically consistent pore depths, such as Figure 7 As shown, the Luan-shaped pore depth will not suddenly change in diameter like the peak-shaped pore. Therefore, the local resistance caused by the diameter change can be reduced, which is conducive to the entry of vapor phase silicon deposition precursor molecules (such as silane molecules) and improves the silicon loading efficiency.

[0052] The porous carbon provided by the present invention has pores with a diameter of less than 3 nm accounting for more than 85%, and in the range of pore diameters of 1-3 nm, the pore diameter distribution is a Luan-shaped distribution, the pore resistance is small, and the silicon loading efficiency is high. The silicon-carbon negative electrode material prepared using the porous carbon has good electrochemical performance.

[0053] In some specific embodiments of the present invention, the pore distribution curve of the porous carbon has at least one peak in the pore size range of 1-3 nm; and / or, the porous carbon has at least one peak and valley in the pore size range of 1-3 nm, and the differential pore volume dV / dW of the lowest point of the peak and valley is greater than 0.1 cm 3 ·g -1 ·nm -1 The pore distribution is more uniform, which is more conducive to the entry of vapor phase silicon precursor molecules (such as silane molecules) and the deposition of nano-silicon.

[0054] In some specific embodiments of the present invention, the microporosity of the porous carbon is 50-90%, for example, it can be 50%, 60%, 70%, 80%, 90%, etc., or it can be other values ​​within the range; the pore volume of pores (micropores) with a pore size <2nm is controlled to account for 50-90%, on the one hand, to provide sufficient adsorption pores and ensure the adsorption force field, so as to facilitate the adsorption and cracking of nano-silicon into the pores; on the other hand, to avoid the porous carbon with high microporosity (for example, microporosity>90%) showing the phenomenon of easy entry and difficult exit during the deintercalation of lithium ions.

[0055] In some specific embodiments of the present invention, the pore volume of the porous carbon is greater than or equal to 0.6cc / g, for example, it can be 0.6cc / g, 0.7cc / g, 0.8cc / g, 0.9cc / g, 1.0cc / g, 1.1cc / g, 1.2cc / g, etc., or other values ​​within the range; in some specific embodiments, the pore volume of the porous carbon is 0.6-1.2cc / g; the pore volume affects the silicon loading, and a higher silicon content can obtain sufficiently high capacity and efficiency.

[0056] In some embodiments of the present invention, the BET specific surface area of ​​the porous carbon is 1500-2500 m 2 / g, for example, it can be 1500m 2 / g、1600m 2 / g、1800m 2 / g, 2000m 2 / g, 2200m 2 / g、2500m 2 / g, etc., or other values ​​within the range.

[0057] In some specific embodiments of the present invention, the particle size Dv50 of the porous carbon is 3-10μm, for example, 3μm, 5μm, 7μm, 9μm, 10μm, etc., or other values ​​within the range; the particle size Dv99 of the porous carbon is 10-25μm, for example, 10μm, 15μm, 20μm, 25μm, etc., or other values ​​within the range; the particle size Dn10 of the porous carbon is 0.5-5μm, for example, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, etc., or other values ​​within the range.

[0058] In some specific embodiments of the present invention, the porous carbon includes at least one of biomass-derived carbon, resin-derived carbon, petroleum coke-derived carbon, coal-derived carbon, metal-modified carbon materials, and metal oxide-modified carbon materials.

[0059] In some specific embodiments of the present invention, the porous carbon can be selected from commercial specification products, or prepared by methods known in the art, such as hydrothermal method, solvothermal method, electrochemical deposition method, powder metallurgy method, molten metal method, ion exchange method, activation method, etc.

[0060] The method for preparing porous carbon in the specific embodiment of the present invention is described by taking the following method for preparing porous carbon as an example, but is not limited thereto, and any other method for preparing porous carbon may be used.

[0061] The method for preparing the porous carbon comprises the following steps:

[0062] (1) Dry the mangosteen peel and grind it into powder.

[0063] (2) The powder obtained in step (1) is stirred in HCl, then washed with deionized water until the water becomes colorless, and dried.

[0064] (3) The dried mangosteen peel powder and KOH in step (2) are uniformly dispersed in water at a mass ratio of 1:1-1:4, stirred, and then freeze-dried to remove moisture.

[0065] (4) The mixed precursor obtained in step (3) is then heated in a tube furnace at 200, 300, and 400° C. for 1.5 h, respectively, and then at 600-1000° C. for 1 h, in argon gas.

[0066] (5) Finally, the calcined product is washed with deionized water and dried in vacuum to obtain the porous carbon.

[0067] In some specific embodiments of the present invention, step (5) further comprises a screening process after vacuum drying.

[0068] In some specific embodiments of the present invention, the particle size distribution of the porous carbon can be regulated by grinding into powder in step (1) and / or sieving after vacuum drying in step (5). This is well known in the art and will not be described in detail.

[0069] A second aspect of the present invention provides a silicon-carbon negative electrode material, which includes the porous carbon described in any one of the aforementioned embodiments, and nano-silicon located in the pores of the porous carbon.

[0070] In the present invention, the nano silicon is a silicon material having at least one dimension less than 100 nm. For example, at least one dimension of the nano silicon is 99 nm, 90 nm, 80 nm, 70 nm, 60 nm, 50 nm, 40 nm, 30 nm, 20 nm, 10 nm, 9 nm, 8 nm, 7 nm, 6 nm, 5 nm, 4 nm, 3 nm, 2 nm, 1.5 nm, 1 nm, 0.5 nm, 0.1 nm, 0.01 nm, etc., or other values ​​within the range.

[0071] In some specific embodiments of the present invention, nano-silicon may be nano-silicon particles having a crystal domain size of 0 nm to 3 nm, specifically 0.01 nm, 0.1 nm, 0.5 nm, 1 nm, 2 nm, 3 nm or any value between 0 nm and 3 nm; small particles have a higher specific surface area and a shorter diffusion path, can release pressure faster, and reduce the degree of volume expansion, which is beneficial to the improvement of coulombic efficiency.

[0072] The silicon-carbon negative electrode material provided by the present invention has high capacity, high initial efficiency and low expansion rate.

[0073] In some specific embodiments of the present invention, the particle size Dv50 of the silicon-carbon negative electrode material is 3 to 10 μm, for example, any point value among 3 μm, 5 μm, 7 μm, 9 μm, and 10 μm, or a range value composed of any two point values; the particle size Dv99 of the silicon-carbon negative electrode material is 10-25 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm, etc., or other values ​​within the range; the particle size Dn10 of the silicon-carbon negative electrode material is 0.5-5 μm, for example, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc., or other values ​​within the range.

[0074] In some specific embodiments of the present invention, the BET specific surface area of ​​the silicon-carbon negative electrode material is 0.5-30 m 2 / g, for example, it can be 30m 2 / g, 25m 2 / g, 20m 2 / g, 15m 2 / g, 10m2 / g, 5m 2 / g, 4.9m 2 / g, 4.7m 2 / g, 4.5m 2 / g, 4.2m 2 / g, 4m 2 / g, 3.5m 2 / g, 3m 2 / g, 2.5m 2 / g, 2m 2 / g, 1m 2 / g, 0.5m 2 / g, etc., or other values ​​within the range.

[0075] In some specific embodiments of the present invention, the tap density of the silicon-carbon negative electrode material is 0.5-2 g / cm 3 , for example, it can be 0.5 g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.75g / cm 3 , 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2g / cm 3 Etc., or other values ​​within the range.

[0076] In some specific embodiments of the present invention, the surface of the silicon-carbon negative electrode material further includes a coating layer; the coating layer includes at least one of amorphous carbon, a fast ion conductor and a high molecular polymer. The present invention further coats the surface of the silicon-carbon negative electrode material with the coating layer to further improve the electrical properties of the silicon-carbon negative electrode material.

[0077] In some specific embodiments of the present invention, the silicon content of the silicon-carbon negative electrode material is 5wt%-85wt%, for example, it can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, etc., or it can be other values ​​within the range.

[0078] In some specific embodiments of the present invention, the silicon content of the silicon-carbon negative electrode material may be 40wt%-60wt%.

[0079] In some specific embodiments of the present invention, the method for preparing the silicon-carbon negative electrode material comprises the following steps: vapor-depositing porous carbon in an atmosphere containing a silicon source to obtain the silicon-carbon negative electrode material.

[0080] In some specific embodiments of the present invention, the temperature of the vapor deposition is 300-1200°C, for example, it can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc., or it can be other values ​​within the range.

[0081] In some specific embodiments of the present invention, the silicon source can be one or more of monosilane, disilane, trisilane, dimethylsilane, hexamethyldisilane, dichlorodihydrosilane, trichlorosilane, silicon tetrachloride, and silicon tetrafluoride.

[0082] In some specific embodiments of the present invention, the silicon-carbon negative electrode material is coated to obtain a coating layer on the surface of the silicon-carbon negative electrode material, and the coating layer contains at least one of amorphous carbon, a fast ion conductor and a high molecular polymer.

[0083] In some specific embodiments of the present invention, the coating layer includes a carbon coating layer, and the carbon coating layer is obtained by chemical vapor deposition, in which a gaseous carbon source is introduced under a protective gas atmosphere to carbon-coat the porous carbon after silicon deposition.

[0084] In some specific embodiments of the present invention, the temperature of carbon coating is 300-1200°C, for example, it can be 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc., or other values ​​within the range; the deposition time of carbon coating is 20min-6h, for example, 20min, 1h, 2h, 3h, 4h, 5h, 6h, etc., or other values ​​within the range.

[0085] In some specific embodiments of the present invention, the gaseous carbon source may be at least one of acetylene, methane, ethane or ethylene. In other embodiments, other carbon sources may also be used.

[0086] A third aspect of the present invention provides an electrode sheet, which includes the silicon-carbon negative electrode material described in any one of the aforementioned embodiments.

[0087] A fourth aspect of the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the electrode sheet described in the above embodiment.

[0088] A fifth aspect of the present invention provides an electrical appliance, which includes the lithium-ion battery described in the above embodiment.

[0089] The following is a detailed description of some embodiments of the present invention in conjunction with specific examples. The raw materials used in the examples can be purchased from the market unless otherwise specified.

[0090] Example 1

[0091] S1. Preparation of porous carbon:

[0092] (1) Dry the mangosteen peel at 80°C for 24 h and grind it into powder;

[0093] (2) Stir in 1 M HCl overnight, then wash with deionized water until the water is colorless, and dry at 80 °C for 12 h;

[0094] (3) evenly dispersing the dried mangosteen peel powder and KOH in water at a mass ratio of 1:3, stirring overnight, and then freeze-drying to remove moisture;

[0095] (4) the mixed precursor was then heated in a tube furnace at 200, 300, and 400 °C for 1.5 h, respectively, and then at 850 °C for 1 h in argon at a heating rate of 3 °C / min;

[0096] (5) Finally, the calcined product was washed with deionized water, dried in vacuum at 80° C. for 12 h, and sieved to obtain the porous carbon.

[0097] The particle size Dv50 of the porous carbon in this embodiment is 6.6 μm, Dv99 is 16.2 μm, and Dn10 is 3.3 μm; the specific surface area, pore volume and pore structure information are shown in Table 1;

[0098] Depend on Figure 1 It can be seen that the pore distribution of the porous carbon in the present embodiment in the range of 1-3 nm is a Luan-shaped distribution;

[0099] S2. Vapor-phase silicon deposition: The porous carbon was placed in a rotary furnace, heated to 100°C, and kept warm for 30 min under vacuum. Then, nitrogen was introduced for protection. The temperature was then raised to 550°C at a rate of 5°C / min. Then, monosilane (SiH4) was introduced at a flow rate of 10 L / min for 4 h. After the reaction was completed, the silicon source valve was closed.

[0100] S3. Carbon coating: After silicon deposition is completed, the temperature is raised to 700°C, and acetylene (C2H2) is introduced at a flow rate of 5L / min. The acetylene is introduced for 3 hours to obtain a silicon-carbon negative electrode material.

[0101] Example 2

[0102] The preparation method of the negative electrode material provided in this embodiment refers to that in Example 1, except that:

[0103] Preparation of porous carbon in this embodiment:

[0104] (1) Dry the mangosteen peel at 80°C for 24 h and grind it into powder;

[0105] (2) Stir in 1 M HCl overnight, then wash with deionized water until the water is colorless, and dry at 80 °C for 12 h;

[0106] (3) evenly dispersing the dried mangosteen peel powder and KOH in water at a mass ratio of 1:2, stirring overnight, and then freeze-drying to remove moisture;

[0107] (4) the mixed precursor was then heated in a tube furnace at 200, 300, and 400 °C for 1.5 h, respectively, and then at 680 °C for 1 h in argon at a heating rate of 3 °C / min;

[0108] (5) Finally, the calcined product was washed with deionized water, dried in vacuum at 80° C. for 12 h, and sieved to obtain the porous carbon.

[0109] The particle size Dv50 of the porous carbon in this embodiment is 7.5 μm, Dv99 is 16.9 μm, and Dn10 is 0.5 μm; the specific surface area, pore volume and pore structure information are shown in Table 1;

[0110] Depend on Figure 2 It can be seen that the pore distribution of the porous carbon in this embodiment in the range of 1-3 nm is Luan-shaped.

[0111] Example 3

[0112] The preparation method of the negative electrode material provided in this embodiment refers to that in Example 1, except that:

[0113] Preparation of porous carbon in this embodiment:

[0114] (1) Dry the mangosteen peel at 80°C for 24 h and grind it into powder;

[0115] (2) Stir in 1 M HCl overnight, then wash with deionized water until the water is colorless, and dry at 80 °C for 12 h;

[0116] (3) evenly dispersing the dried mangosteen peel powder and KOH in water at a mass ratio of 1:2.5, stirring overnight, and then freeze-drying to remove moisture;

[0117] (4) the mixed precursor was then heated in a tube furnace at 200, 300, and 400 °C for 1.5 h, respectively, and then at 730 °C for 1 h in argon at a heating rate of 3 °C / min;

[0118] (5) Finally, the calcined product was washed with deionized water, dried in vacuum at 80° C. for 12 h, and sieved to obtain the porous carbon.

[0119] The particle size Dv50 of the porous carbon in this embodiment is 5.5 μm, Dv99 is 15.2 μm, and Dn10 is 0.5 μm; the specific surface area, pore volume and pore structure information are shown in Table 1;

[0120] Depend on Figure 3 It can be seen that the pore distribution of the porous carbon in this embodiment in the range of 1-3 nm is Luan-shaped.

[0121] Example 4

[0122] The preparation method of the negative electrode material provided in this embodiment refers to that in Example 1, except that:

[0123] Preparation of porous carbon in this embodiment:

[0124] (1) Dry the mangosteen peel at 80°C for 24 h and grind it into powder.

[0125] (2) Stir in 1 M HCl overnight, then wash with deionized water until the water is colorless, and dry at 80 °C for 12 h.

[0126] (3) The dried mangosteen peel powder and KOH were uniformly dispersed in water at a mass ratio of 1:1.5, stirred overnight, and then freeze-dried to remove moisture.

[0127] (4) The mixed precursor was then heated in a tube furnace at 200, 300, and 400 °C for 1.5 h, respectively, and then at 600 °C for 1 h at a heating rate of 3 °C / min in argon.

[0128] (5) Finally, the calcined product was washed with deionized water, dried in vacuum at 80° C. for 12 h, and sieved to obtain the porous carbon.

[0129] The particle size Dv50 of the porous carbon in this embodiment is 6.5 μm, Dv99 is 17.2 μm, and Dn10 is 2.3 μm; the specific surface area, pore volume and pore structure information are shown in Table 1.

[0130] The pore distribution of the porous carbon in the range of 1-3 nm is Luan-shaped.

[0131] Comparative Example 1

[0132] The difference between the preparation method of the silicon-carbon negative electrode material in Comparative Example 1 and Example 1 is that the porous carbon used for vapor phase silicon deposition is different. The porous carbon used in Comparative Example 1 was purchased from Tianjin Chenxiang Fengkai Company, model G25; the remaining process parameters of vapor phase silicon deposition and carbon coating are the same as in Example 1.

[0133] The particle size Dv50 of the porous carbon in Comparative Example 1 is 6.2 μm, Dv99 is 21 μm, and Dn10 is 2.4 μm; the specific surface area, pore volume and pore structure information are shown in Table 1;

[0134] Depend on Figure 4 It can be seen that the pore distribution of the porous carbon in this comparative example in the range of 1-3 nm presents a peak distribution.

[0135] Comparative Example 2

[0136] The difference between the preparation method of the silicon-carbon negative electrode material in Comparative Example 2 and Example 1 is that the porous carbon used for vapor phase silicon deposition is different. The porous carbon used in Comparative Example 2 is provided by Jiangsu Pushida Company; the remaining process parameters of vapor phase silicon deposition and carbon coating are the same as those in Example 1.

[0137] The particle size Dv50 of the porous carbon in Comparative Example 2 is 7.6 μm, Dv99 is 18.9 μm, and Dn10 is 2.6 μm; the specific surface area, pore volume and pore structure information are shown in Table 1;

[0138] Depend on Figure 5 It can be seen that the pore distribution of the porous carbon in this comparative example in the range of 1-3 nm is Luan-shaped.

[0139] Comparative Example 3

[0140] The difference between the preparation method of the silicon-carbon negative electrode material in Comparative Example 3 and Example 1 is that the porous carbon used for vapor phase silicon deposition is different, and the porous carbon used in Comparative Example 3 is provided by Fujian Tianli Company; the remaining process parameters of vapor phase silicon deposition and carbon coating are the same as in Example 1.

[0141] The particle size Dv50 of the porous carbon in Comparative Example 3 is 6.5 μm, Dv99 is 19.1 μm, and Dn10 is 3.0 μm; the specific surface area, pore volume and pore structure information are shown in Table 1;

[0142] Depend on Figure 6It can be seen that the pore distribution of the porous carbon in this comparative example in the range of 1-3 nm presents a peak distribution.

[0143] Comparative Example 4

[0144] The difference between the preparation method of the silicon-carbon negative electrode material in Comparative Example 4 and Example 1 is that the porous carbon used for vapor phase silicon deposition is different, and the activated carbon used in Comparative Example 4 is provided by Jiangsu Pushida Company; the remaining process parameters of vapor phase silicon deposition and carbon coating are the same as those in Example 1.

[0145] The particle size Dv50 of the porous carbon in Comparative Example 4 is 7.6 μm, Dv99 is 18.9 μm, and Dn10 is 0.6 μm; the specific surface area, pore volume and pore structure information are shown in Table 1.

[0146] Test example

[0147] (1) Specific surface area, pore volume and pore ratio test of porous carbon

[0148] The specific surface area, pore volume and pore ratio of the porous carbon in each embodiment and each comparative example were tested by BET method according to GB / T 19587-2017; ASAP 2460 (from Micromeritics) was used for measurement, which works according to the Sorption Method with Adaptive dosing Rate (SMART method). As for reference materials, standard material GB13905 (9.01 m 2 / g, based on multi-point BET method), GB13913 (5.78m 2 / g, based on multi-point BET method) and GB13909 (specific surface area, total pore volume and pore size standard materials of mesoporous SIO2).

[0149] To reduce the dead volume, filler rods are added to the reference and sample test tubes. The test tubes are mounted on the BET device. The saturated vapor pressure of nitrogen (N2 4.0) is determined. A certain amount of sample is weighed into the glass test tube so that the test tube containing the filler rod is completely filled and the minimum dead volume is produced. To dry the sample, the sample is kept under vacuum at 200°C for 2 hours. After cooling, the sample weight is recorded. The glass test tube containing the sample is mounted on the measuring device. To degas the sample, it is evacuated at a selected pumping speed so that no material is sucked into the pump, reaching a final pressure of 200mTorr.

[0150] Test method: Nitrogen adsorption measurements were performed using a Micromeritics ASAP 2460 instrument at liquid nitrogen temperature (77.3K). Prior to the measurement, the sample was degassed at 443K until a static vacuum of less than 0.01 Torr was reached. The adsorption site distribution was calculated based on the adsorption isotherm using the standard instrument software DFT. (NLDFT) software.

[0151] Pore ​​ratio test method: Nitrogen adsorption method is used to test the percentage of pore volume with pore diameter less than 3nm or less than 0.7nm in porous carbon to the total pore volume, or the percentage of other pores (volume).

[0152] The test results are shown in Table 1.

[0153] Table 1

[0154]

[0155] (2) Testing of particle size, specific surface area, tap density, silicon content and silane utilization of silicon-carbon anode materials

[0156] Test method:

[0157] Specific surface area: The specific surface area of ​​silicon carbon in each embodiment and each comparative example was tested by the BET method according to GB / T 19587-2017;

[0158] Test method: Nitrogen adsorption measurements were performed using a Micromeritics ASAP 2460 instrument at liquid nitrogen temperature (77.3K). Prior to the measurement, the sample was degassed at 443K until a static vacuum of less than 0.01 Torr was reached. The adsorption site distribution was calculated based on the adsorption isotherm using the standard instrument software DFT. (NLDFT) software. In order to reduce the dead volume, filler rods were added to the reference test tube and the sample test tube (the specific test method is the same as the test method for the specific surface area of ​​porous carbon).

[0159] Particle size: tested using Malvern 3000 equipment, according to the national standard GB / T 19077-2016.

[0160] Tap density: tested using Dandong Better BT313 tap density tester, tested according to national standard GB / T24533-2019.

[0161] Silicon content:

[0162] The silicon content is measured by calcining at 1000℃ in air for 1 hour using a thermogravimetric analyzer to completely oxidize the carbon and convert the silicon into silicon dioxide. The weight of the added oxygen is then used to calculate the silicon content in the silicon-carbon material. The details are as follows:

[0163] (1) Weigh about 2 g of silicon-carbon material, with the actual mass recorded as m0; and place it in a crucible with a mass of m1;

[0164] (2) Place the crucible in a tube furnace or muffle furnace, continue to pass compressed air, raise the temperature to 600°C at 10°C / min, hold for 1 hour, then raise the temperature to 1000°C at the same rate and hold for 1 hour;

[0165] (3) After cooling naturally to room temperature, take out the crucible and weigh its mass m2;

[0166] (4) Calculate Si content Si% = (m2-m1) × MSi÷MSiO2÷m0×100%;

[0167] Note: MSiO2 is the relative molecular mass of SiO2, 60.084 g / mol; MSi is the relative molecular mass of Si, 28.0855 g / mol.

[0168] Silane utilization % = [received material amount (g) × silicon content (%)] / [volume of silane introduced (L) × silane density (g / L)].

[0169] The test results are shown in Table 2.

[0170] Table 2

[0171]

[0172]

[0173] (3) Electrochemical performance test

[0174] Preparation method of button half-cell: active material: SP: CNT: PAA glue is mixed in a mass ratio of 80:9:1:10, made into a slurry with deionized water, evenly coated on a copper foil, and vacuum dried at 80°C for 24 hours to obtain the battery electrode for the experiment. Then, a lithium sheet is used as a counter electrode, and an electrolyte of 1.1 mol / L LiPF6 is used. The solvent is a four-component mixed solvent, ethylene carbonate (EC): vinylene carbonate (VC): dimethyl carbonate (DMC): fluoroethylene carbonate (FEC) = 1:1:1:1 (volume ratio). A polypropylene microporous film is used as a diaphragm and assembled into a CR2025 button half-cell in a vacuum glove box.

[0175] The battery performance test method is: use a battery test system (half-battery test American Arbin multi-channel battery test system, German Braun Company Labstar (1200 / 780) glove box) to test the capacity and the first charge and discharge efficiency (first efficiency).

[0176] The test steps are: 0.1C DC to 5mV, let stand for 5min; 0.02C DC to 5mV, let stand for 5min; 0.01C DCto 5mV, let stand for 5min; 0.1C CC to 0.8V, 0.1C CC to 2V.

[0177] The test results are shown in Table 3.

[0178] Table 3

[0179]

[0180]

[0181] It can be seen from the data in Table 3 that the capacity and initial efficiency of the lithium-ion battery assembled using the silicon-carbon negative electrode material prepared using the porous carbon in the present invention are significantly improved.

[0182] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A porous carbon, characterized in that The porous carbon includes micropores and mesopores, and the percentage of pore volume of pores with pore diameter less than 3 nm in the total pore volume is higher than 85%, and the percentage of pore volume of pores with pore diameter less than 0.7 nm in the total pore volume is lower than 15%; in a pore distribution curve obtained by nitrogen adsorption test, the abscissa is the pore diameter and the ordinate is the differential pore volume dV / dW, the porous carbon has a differential pore volume dV / dW>0.05cm in the pore diameter range of 1-3 nm. 3 ·g -1 ·nm -1 .

2. The porous carbon according to claim 1, characterized in that The porous carbon has at least one peak in the range of pore diameter of 1-3 nm; And / or, the porous carbon has at least one peak-valley in the pore diameter range of 1-3 nm, and the differential pore volume dV / dW of the lowest point of the peak-valley is greater than 0.1 cm 3 ·g -1 ·nm -1 .

3. The porous carbon according to claim 1, characterized in that The microporosity of the porous carbon is 50-90%.

4. The porous carbon according to claim 1, characterized in that Contains at least one of the following characteristics: (1) The pore volume of the porous carbon is 0.6-1.2 cc / g; (2) The BET specific surface area of ​​the porous carbon is 1500-2500 m 2 / g; (3) The particle size Dv50 of the porous carbon is 3-10 μm, the particle size Dv99 of the porous carbon is 10-25 μm, and the particle size Dn10 of the porous carbon is 0.5-5 μm.

5. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material comprises the porous carbon according to any one of claims 1 to 4, and nano-silicon located in the pores of the porous carbon.

6. The silicon-carbon negative electrode material according to claim 5, characterized in that: Contains at least one of the following characteristics: (1) The particle size Dv50 of the silicon-carbon negative electrode material is 3 to 10 μm, the particle size Dv99 of the silicon-carbon negative electrode material is 10 to 25 μm, and the particle size Dn10 of the silicon-carbon negative electrode material is 0.5 to 5 μm; (2) The BET specific surface area of ​​the silicon-carbon negative electrode material is 0.5-30 m 2 / g; (3) The tap density of the silicon-carbon negative electrode material is 0.5-2 g / cm 3 ; (4) The surface of the silicon-carbon negative electrode material further includes a coating layer; the coating layer comprises at least one of amorphous carbon, a fast ion conductor and a high molecular polymer; (5) The silicon content of the silicon-carbon negative electrode material is 5wt%-85wt%.

7. The method for preparing the silicon-carbon negative electrode material according to claim 5 or 6, characterized in that: The following steps are involved: The porous carbon is vapor-deposited in an atmosphere containing a silicon source to obtain the silicon-carbon negative electrode material.

8. The method for preparing the silicon-carbon negative electrode material according to claim 7, characterized in that: Also includes: The silicon-carbon negative electrode material is subjected to coating treatment to obtain a coating layer on the surface of the silicon-carbon negative electrode material, wherein the coating layer contains at least one of amorphous carbon, a fast ion conductor and a high molecular polymer.

9. An electrode sheet, characterized in that: The electrode sheet comprises the silicon-carbon negative electrode material according to claim 5 or 6.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the electrode sheet according to claim 9.

11. An electrical appliance, characterized in that: The electrical appliance comprises the lithium-ion battery according to claim 10.

Citation Information

Patent Citations

  • Mesoporous carbon / silicon composite anode material and preparation method thereof

    CN102867944A

  • Porous carbon material and preparation method and application thereof

    CN103420353A

  • Preparation method of biomass-based graded porous carbon

    CN115571880A

  • Preparation method and application of high-performance room-temperature sodium-sulfur battery positive electrode material

    CN116553520A

  • Negative electrode material, preparation method thereof and lithium ion battery

    CN117317205A

Cited By

  • Negative electrode material and preparation method thereof, secondary battery and electronic device

    CN119965252A

  • Porous carbon particle and preparation method thereof, negative electrode active material and secondary battery

    CN121282198A

  • Porous carbon, silicon-carbon negative electrode material, electrode sheet, lithium-ion battery, and electric device

    WO2026067541A1